Ureterovaginal fistula following spontaneous vaginal delivery, repaired by vaginal ureteroneocystostomy in a low resource setting - Lengmang, Sunday J (J Surg Case Rep, 2017)
Ureterovaginal fistula commonly follows ureteric injury during pelvic surgery, and presents with continuous urinary incontinence in spite of normal micturition. Continuous urinary incontinence has significant impact on quality of life, thus requiring effective surgical intervention in order to restore health. We found no reported case of ureterovaginal fistula following spontaneous vaginal delivery with prolonged obstructed labour. Relevant history and simple diagnostic procedures were used for diagnosis and the patient had successful vaginal ureteroneocystostomy. This could be the first reported ureterovaginal fistula following spontaneous vaginal delivery with prolonged obstructed labour. Vaginal ureteroneocystostomy though scarcely reported, is feasible in selected cases.